Evaluation of oral meloxicam in beef calves with neonatal calf diarrhea - Neill, Hannah (My University, 2025)
Objective To examine behavioral and physiologic outcomes associated with the expression of pain in calves with naturally occurring neonatal calf diarrhea (NCD) and determine the impact of meloxicam administration on reducing these pain-related behaviors and outcomes. Methods Beef calves 3 to 30 days old with NCD and no comorbidities or prior NSAID or steroid administration were enrolled as clinical cases, and healthy beef calves were enrolled as controls. Clinical cases received either meloxicam (MEL group) or placebo (PLBO group) treatment; all controls received placebo. Over 7 time points, outcomes measured were substance P, prostaglandin E metabolite, mechanical nociceptive threshold, gait analysis, behavior analysis, physical examinations, and intake bloodwork. Results 20 calves with NCD and 8 healthy calves were enrolled. Prostaglandin E metabolite was significantly higher in calves with NCD than controls. Control calves were more reactive to pressure over the hip than calves with NCD, particularly those treated with meloxicam. Calves with NCD had shorter stride length and slower gait velocity compared to controls. Calves with NCD spent more time lying and more time lying with their head up compared to controls. Calves in the MEL group spent more time lying with their head down compared to PLBO calves. Conclusions Differences in mechanical nociceptive threshold, gait analysis, and lying behavior possibly indicated the presence of abdominal pain. Differences in head posture between MEL and PLBO calves suggest that calves treated with meloxicam may have been more comfortable. Clinical Relevance Calves with NCD may experience pain, and treating them with meloxicam may relieve that pain.
Keywords: Meloxicam; Beef calf; Diarrhea